2007
DOI: 10.1038/sj.clpt.6100021
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Population PK–PD Model of Ispinesib-induced Myelosuppression

Abstract: The goal of the present analysis is to fit a Bayesian population pharmacokinetic pharmacodynomic (PK-PD) model to characterize the relationship between the concentration of ispinesib and changes in absolute neutrophil counts (ANC). Ispinesib, a kinesin spindle protein (KSP) inhibitor, blocks assembly of a functional mitotic spindle, leading to G2/M arrest. A first time in human, phase I open-label, non-randomized, dose-escalating study evaluated ispinesib at doses ranging from 1 to 21 mg/m(2). PK-PD data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Actually, the estimates of the typical values of the system-related parameters, Circ 0 , MTT and γ, were similar to those obtained previously (14,21,23,(26)(27)(28)(29)(30)36,45,46,55,57), including MTT, which was estimated at the lower end of the values found in other studies (14,26). In addition, the graphical exploratory analysis of the effect of body weight, age, serum creatinine, alkalyne phosphatase, ALT, AST, LDH, total bilirubin and total proteins on the model parameter did not evidence any statistical significant correlation, which is consistent with the results of a recent publication where these covariates were not statistically associated or had no clinically relevant effect on the model parameters derived for docetaxel, paclitaxel etoposide and topotecan (27).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Actually, the estimates of the typical values of the system-related parameters, Circ 0 , MTT and γ, were similar to those obtained previously (14,21,23,(26)(27)(28)(29)(30)36,45,46,55,57), including MTT, which was estimated at the lower end of the values found in other studies (14,26). In addition, the graphical exploratory analysis of the effect of body weight, age, serum creatinine, alkalyne phosphatase, ALT, AST, LDH, total bilirubin and total proteins on the model parameter did not evidence any statistical significant correlation, which is consistent with the results of a recent publication where these covariates were not statistically associated or had no clinically relevant effect on the model parameters derived for docetaxel, paclitaxel etoposide and topotecan (27).…”
Section: Discussionsupporting
confidence: 54%
“…Initially, the model was successfully applied to different drugs such as docetaxel, paclitaxel, etoposide, 2-deoxy-2-methylidenecytidine, irinotecan and vinflunine (14). Later, it was applied to topotecan in adult (30) and pediatric populations (36), indisulam (57), pemetrexed (28,29), diflomotecan (55), ispinesib (26), trabectedin (21) and the combinations epirubicin-docetaxel (46) and fluorouracilepirrubicin-cyclophosphamide (45). However, this model has not been applied yet to analyze the ANC data following HDC and PBSC transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Five hundred data sets were simulated from the model and the confidence interval (shadow area) for the calculated median and 95% prediction interval were superimposed on the observed data (dots).The black lines are the corresponding median and 95% percentiles of the observed data authors stated in the development of the original model an Emax model was superior to a linear model for docetaxel [5]. Even though the data in this study supported a more complex drug-effect model, a few publications [7,12,14,25,29,42] have tested an Emax model for other types of anti-cancer drugs, but have not found it to significantly improve the fit. Then again, in this study of docetaxel an Emax model showed a relative low reduction in OFV, while a sigmoid Emax model greatly improved the fit.…”
Section: Discussionmentioning
confidence: 90%
“…This model has since the original publication been successfully applied to both leukocyte and neutrophil measurements following several additional anti-cancer drugs and regimens [6][7][8][9][10][11][12][13][14][15][16]. It has also been shown to satisfactorily describe thrombocyte and lymphocyte measurements following chemotherapy [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…With respect to the system related parameters, the estimated of Circ 0 was consistent with ANC normal values. The MTT could not be estimated correctly with the available data and, therefore, was fixed to 118 h as previously reported in the literature (30,(44)(45)(46)(47)(48). The estimated γ value, 0.135, was also similar to those obtained previously for other anticancer drugs, such as irinotecan (0.132) or topotecan (0.120) (30,49).…”
Section: Discussionmentioning
confidence: 71%